2021
DOI: 10.1088/1361-6579/ac05d5
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of continuous respiratory rate monitoring in predicting hypoxic and pyrexic events: a retrospective cohort study

Abstract: Respiratory rate (RR) is routinely used to monitor patients with infectious, cardiac and respiratory diseases and is a component of early warning scores used to predict patient deterioration. However, it is often measured visually with considerable bias and inaccuracy. Objectives: Firstly, to compare distribution and accuracy of electronically measured RR (EMRR) and visually measured RR (VMRR). Secondly, to determine whether, and how far in advance, continuous electronic RR monitoring can predict oncoming hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…This is also aligned with a study that used RespiraSense in a group of patients with infectious respiratory disease in a tertiary hospital in Dublin (Ireland). The study showed that an increased RR had a hazard ratio of 1.8 (95% confidence interval 1.05–3.70) for desaturation in the next 12 h [ 15 ]. Because of the limited clinal data for effectiveness of ARRM (and RespiraSense) compared with IM, an effectiveness threshold analysis was performed to understand the robustness of results based on variation in the effect size.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is also aligned with a study that used RespiraSense in a group of patients with infectious respiratory disease in a tertiary hospital in Dublin (Ireland). The study showed that an increased RR had a hazard ratio of 1.8 (95% confidence interval 1.05–3.70) for desaturation in the next 12 h [ 15 ]. Because of the limited clinal data for effectiveness of ARRM (and RespiraSense) compared with IM, an effectiveness threshold analysis was performed to understand the robustness of results based on variation in the effect size.…”
Section: Methodsmentioning
confidence: 99%
“…RespiraSense™ is a non-invasive, wireless, body worn, motion-tolerant, and continuous respiratory rate monitor [ 14 ]. It measures the mechanics of breathing by analysing the movements of the chest and abdomen using proprietary piezo film sensors [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Respiratory rate may be the vital sign that most accurately predicts outcome [ 57 ], yet manual values are often inaccurate [ 58 ] and correlate poorly with machine-measured values [ 59 ]. Although machine-measured values should be the best predictors of deterioration and mortality [ 59 , 60 ], others have found that manual recordings may be better because they are biased by a nurse’s more accurate intuitive judgment of how sick the patient is [ 61 ]. The assessment of mental status required by NEWS may also be inadequate and more thorough screening for delirium has been suggested [ 62 ].…”
Section: Other News Shortcomingsmentioning
confidence: 99%
“…Internationally CVW+cRR has become an alternative way of providing care to high-risk patients using a combination of specialist care and telehealth, employing "systems, staffing, and daily routines of a hospital ward…" in a community-based care model [9,10]. However, as we attempted to answer the challenge statement -"How might we empower people with exacerbating COPD to become a partner in the management of their health and ensure that they receive the right care at the right time as close to home as possible?"…”
Section: A Design Thinking Approach To Pathway Creationmentioning
confidence: 99%
“…Published evidence demonstrates that cRR was able to predict patients who became de-saturated (SpO 2 <92%) and those who developed a fever (38 0 Celsius) 12 hours earlier when rates stayed elevated above 24 breaths per minute for 30 minutes or longer [10].…”
Section: Respirasense Tm -Continuous Respiratory Rate (Crr) Monitoringmentioning
confidence: 99%